(untitled) (Contemporary Mathematics, 2024)
As a pivotal branch within the realm of differential equations, the theory of oscillation holds a crucial position in the exploration of natural sciences and the construction of modern control theory Frameworks. In this manuscript, we obtain some oscillatory properties for the noncanonical even-order differential equation with a p-Laplacian-like operator by using comparison with first-order differential inequality. Some examples are discussed to illustrate the effectiveness of our main results.